The Effect of Concentration and Immersion Time Disinfectant on Sterilization Aglaonema Hybrid (Pink Katrina) Leaves - Budiarni, Kasandra; Hindaningrum, Irni Furnawanthi; Muharromah, Restu Siwi; Kartiman, Roni; Novita, Linda; Hardiani, Lany; Elya, Mardoni; Kubil (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2024)
Aglaonema sp. is well known as an ornamental plant in Indonesian society. It has leaf with various beautiful patterns. Aglaonema pink katrina is one of the imported hybrids Aglaonema. A method to increase plant yield quickly is tissue culture. The crucial step in plant tissue culture is sterilization. This study aimed to find the best sterilization method by looking at the effect of concentration and immersion time of sodium hypochlorite (NaOCl) as disinfectant to reduce contaminants explant Aglaonema Pink Katrina leaves. In this study, there were 11 groups consisting of positive control, negative control, and immersion with 2,5; 5%; and 10% NaOCl for 1 minute and 3 minutes. Parameters observed included the time of first contamination, percentage of bacterial and fungal contamination, and appearance of explants for 28 days. The DMRT test showed significant differences in all treatments of disinfectant concentration and soaking time.The results show contamination first time occurred in code S0a (negative control), the highest percentage of sterile explants was in code A5, and explants that were still green/fresh were found in codes A5 and A8 after observation.